Cultivating Religious Inclusiveness through Social Media: Decorating Podcast for Interfaith Dialogue in the "Login Program" - Juhri, Muhammad Alan; Hariani, Hidayah (Digital Muslim Review, 2023)
The discourse of interfaith dialogue between Islam and other religions will always be an interesting issue, especially in the context of multicultural Indonesia. In the digital era, along with the growth of digital preachers who utilise social media, the discourse of interfaith dialogue is also increasingly accessible. As of Ramadan 1444 H, Deddy Corbuzier, an Indonesian podcaster with a large following on YouTube (20.4 million followers), facilitated an interfaith dialogue between interfaith youths named "Login" through his YouTube channel. This paper investigates how this program utilised social media, such as a YouTube podcast, to spread interfaith discourses. Based on online research and digital observation, this paper argues that using YouTube podcasts creatively and innovatively significantly impacts the acceptance of interfaith discourses in a broader context. The Login Program was decorated by humorising sensitive issues, propagating posts with clickbait titles, using hashtags, and maximising thumbnails. In short, by taking the case of the Login program, this article illustrates how interfaith podcasts have achieved great acceptability and become a medium for cultivating religious inclusiveness in Indonesia.